Shift happens : the history of labor in the United States - Mann, J. Albert (Harper, an imprint of HarperCollins Publishers, 2024)
This eye-opening and engaging history of the worker actions that brought us weekends, pay equality, desegregation, an end to child labor and more documents how the labor movement has shaped America and how it intersects with many of the major issues facing modern teens.